Prevalence of hepatitis C and B virus infection in patients with idiopathic dilated cardiomyopathy in Brazil: a pilot study - Reis,Francisco J.F.B. (2007)
The idiopathic dilated cardiomyopathy (IDMC) is a disease of the cardiac muscle characterized by systolic dilation and/or dysfunction of one or both ventricles, symptoms of congestive heart failure and risk of early death. Several studies in animal models and in humans have supported the hypothesis of the viral infection as initial event in the immunopathogenesis of the ventricular dilation. The objective of this study was to correlate the presence of hepatitis C virus chronic infection and idiopathic dilated cardiomyopathy, comparing samples of cases with IDCM with paired controls with Chagas-type specific dilated cardiomyopathy and ischemic-type specific dilated cardiomyopathy. Only 2.9% (1/34) of IDCM patients were HCV carriers, which strongly argue against this hypothesis. Therefore, based on our results, there is no justification for investigating HCV in patients with idiopathic dilated cardiomyopathy diagnosis.